Overreaching Farming through virtual extension techniques - Sharma, J P; Burman, R R; Gill, Reshma (Indian Farming, 2018)
The developments in virtual technology over the past few decades are tremendous and offer great potential in improving access of information to farmers, increased efficiency in production through various measures like effective advisory services, post-production information and market information. The initiatives of virtual extension services have opens up new frontier for agricultural development in India. It can transform the Indian agriculture to a profitable endeavor by reducing the information unevenness and time lag.